Slurry Ice as a Cooling System on 30 GT Fishing Vessel - Alam Baheramsyah; Beni Cahyono; Fransiskus Suganda Aruan (Institut Teknologi Sepuluh Nopember, 2017)
Indonesia is the largest archipelago country in the world that has a sea area that is very spacious. Indonesian sea area is 5.8 million square kilometers and a coastline of 95 181 km has huge potential in the fisheries sector. In line with the need to further improve on the quality of the fish catch. One way to preserve fish is to use a slurry of ice. Slurry ice proved more effective preserving fishery products instead of using ice cubes. Ice slurry cooling system was designed and applied to the fishing vessel 30 GT. The cooling system uses a simple vapor compression system consists of five major components consisting of evaporator, condenser, compressor, and two pumps.In designing this system determined the type of refrigerant used in advance which type of refrigerant R-507a. Then do the design or selection of its main components. The design is only done on the evaporator. As for the other major components such as condensers, compressors, and pumps election in accordance with the specification of the power needed. After that dialakukan depiction of each system component. Then subsequently designing the laying of ice slurry cooling system components on a fishing vessel 30 GT. Through calculations using simple thermodynamic equations obtained cooling load on this system amounted to 32.06 kW. Condenser with a power of 40 kW. Compressor with power 12 kW. Pump with capacity 10 m3 / h. With memepertimbangkan space left on the ship in the ice slurry system design on the main deck of the ship to the efficient use of space on board. The power requirements of the generator vessel increases due to the addition of ice slurry system components therefore do replacement generator into the generator with a power of 100 kW and penambahn fuel tank to 6,000 L.